Small-sided games in the development of technical demands for young hockey goalkeepers - Honório, Samuel (2021)
Introduction: Rink hockey motor learning and control needs deeply study to promote specific motor skills acquisition and knowledge about the game interaction. The complexity of the game suggest the fragmentation to increase the opportunities of interaction among young athletes. Problem Statement and Approach: The objective of this study was to analyse which game model allows for young goalkeepers to have more interventions with the ball and, consequently, a greater number of interactions on the game. Material and Methods: Our study consisted of 24 games analysed, divided in: 8 games in the 3x3model; 8 games in the 4x4model and 8 games in the 5x5 model. The 24 matches were equally divided in the levels of under 8 and under 10 years of age, with a total sample of 88 children. For data collection instrument we used the deferred observation method where we proceeded to a descriptive analysis of the data to find the means, standard deviation and totals of Goalkeeper’s Interventions (GKI). Comparisons were made between game models and athlete’s levels, using the Mann-Whitney and Kruskal -Wallis tests. Results: The results showed that, after the analysis of the total game actions, the 3x3 game model obtained a total of 168 GI actions (21±3,5; p=0,021), the 4x4 model obtained 132(16,50±5,18; p=0,020) and the 5x5 game model obtained 123GI actions(11±2,61; p=0,083). Discussion: According to the results, it was verified that there are statistically significant differences between the 3x3 game and the 5x5 game in the “Under 8” and when compared the small-sided game 4x4 to the formal game 5x5 in the “Under 10 level” in the games analysed we perceive that the small-sided game brings more actions to the game, namely in the actions that the goalkeepers show. Conclusions: The 3x3 game model obtained the highest number of goalkeeper’s actions in both under(and under10, suggesting benefits for improving the technical demands of these young rink hockey goalkeepers.